DOCTRINE OF MAN IN DESCARTES AND PASCAL - A. M. Malivskyi (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose. The paper aims at substantiating the meaningful relationship between Descartes’ and Pascal’s positions as two variants in responding to the demand of the era in the development of anthropology. The realization of this purpose involves defining the spiritual climate of the era and addressing to the texts of two great French thinkers of the 17th century to demonstrate common moments in interpreting the phenomenon of a man. Theoretical basis. The methodological basis in the research is the conceptual propositions of the representatives of phenomenology and hermeneutics. Originality. The existence of the doctrine of human nature by Descartes is argued and the manifestations of common moments with Pascal’s doctrine are outlined. The latter include the context of the Copernican unfinished Revolution, the emphasis on restrictions in the methodology of the natural sciences, the intense search for description language beyond the rational components of human nature, the high opinion in the Christian understanding of man, critique of atheism. Conclusions. The paper substantiates the meaningful relationship in the doctrine of man from both French thinkers, which manifests itself in the vision of the initial situation as a person’s choice of their own foundations in the course of conceptualization the scientific revolution, understanding of Christianity as a basic paradigm of thinking, priority of the anthropological interest over natural-science one, the dominant role of the ethical philosophizing motive.